Animal model of subretinal fibrosis without active choroidal neovascularization. (April 2023) - Zandi, Souska; Li, Yuebing; Jahnke, Laura; Schweri-Olac, Anelia; Ishikawa, Keijiro; Wada, Iori; Nakao, Shintaro; Zinkernagel, Martin S.; Enzmann, Volker
Abstract: Subretinal fibrosis can occur during neovascular age-related macular degeneration (nAMD) and consequently provokes progressing deterioration of AMD patient's vision. Intravitreal anti–vascular endothelial growth factor (VEGF) injections decrease choroidal neovascularization (CNV), however, subretinal fibrosis remains principally unaffected. So far, no successful treatment nor established animal model for subretinal fibrosis exists. In order to investigate the impact of anti-fibrotic compounds on solely fibrosis, we refined a time-dependent animal model of subretinal fibrosis without active choroidal neovascularization (CNV). To induce CNV-related fibrosis, wild-type (WT) mice underwent laser photocoagulation of the retina with rupture of Bruch's membrane. The lesions volume was assessed with optical coherence tomography (OCT). CNV (Isolectin B4) and fibrosis (type 1 collagen) were separately quantified with confocal microscopy of choroidal whole-mounts at every time point post laser induction (day 7–49). In addition, OCT, autofluorescence and fluorescence angiography were carried out at designated timepoints (day 7, 14, 21, 28, 35, 42, 49) to monitor CNV and fibrosis transformation over time. From 21 to 49 days post laser lesion leakage in the fluorescence angiography decreased. Correspondingly, Isolectin B4 decreased in lesions of choroidal flat mounts and type 1 collagen increased. Fibrosis markers, namely vimentin, fibronectin, alpha-smooth muscle actin (α-SMA) and type 1 collagen were detected at different timepoints of tissue repair in choroids and retinas post laser. These results prove that the late phase of the CNV-related fibrosis model enables screening of anti-fibrotic compounds to accelerate the therapeutic advancement for the prevention, reduction, or inhibition of subretinal fibrosis. Highlights: Subretinal fibrosis model of solely fibrosis. Subretinal fibrosis without active choroidal neovascularization (CNV). Screen for urgently needed anti-fibrotic compounds for ocular fibrotic diseases.